2019
DOI: 10.3390/cancers11081183
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Treatment Planning Including Convective Flow in Cerebrospinal Fluid for Brain Tumour Hyperthermia Treatment Using a Novel Dedicated Paediatric Brain Applicator

Abstract: Hyperthermia therapy (40–44 °C) is a promising option to increase efficacy of radiotherapy/chemotherapy for brain tumours, in particular paediatric brain tumours. The Chalmers Hyperthermia Helmet is developed for this purpose. Hyperthermia treatment planning is required for treatment optimisation, but current planning systems do not involve a physically correct model of cerebrospinal fluid (CSF). This study investigates the necessity of fluid modelling for treatment planning. We made treatments plans using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“…Nevertheless, results demonstrated that the degree of control was sufficient for the tumor sites involved, which included bladder, superficial tumors and deep-seated pelvic tumors. Unmet clinical needs are progressing toward more challenging tumor sites such as brain, deep-seated head and neck tumors and peritoneal metastases [94,[422][423][424]. As a result, there is a trend toward device designs providing greater spatial control of the energy deposition to ensure that SAR and temperature distributions in tissues reliably match with rigorous treatment plans to achieve effective treatment of challenging tumor sites, while sparing adjacent critical structures.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, results demonstrated that the degree of control was sufficient for the tumor sites involved, which included bladder, superficial tumors and deep-seated pelvic tumors. Unmet clinical needs are progressing toward more challenging tumor sites such as brain, deep-seated head and neck tumors and peritoneal metastases [94,[422][423][424]. As a result, there is a trend toward device designs providing greater spatial control of the energy deposition to ensure that SAR and temperature distributions in tissues reliably match with rigorous treatment plans to achieve effective treatment of challenging tumor sites, while sparing adjacent critical structures.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…applicators for brain tumors [422] and H&N tumors [121,330,331] based on MW technology, as well as US or MR guided HIFU devices, both for hyperthermia and for thermal ablation. A design challenge for most of these devices is matching the technical and clinical performance of the device with the oncological requirements for the specific site, e.g., the target volume size for gastrointestinal tumors and the need to spare surrounding normal tissue for brain tumors.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A dedicated modelling approach was adopted for the bladder. Recent studies have shown that modelling fluid convection has a large impact on the final temperature distribution, yielding more accurate hyperthermia treatment planning [200,249,250,272]. However, modelling convective heat transfer is computationally time-consuming at this moment, which makes it impractical for routine clinical use.…”
Section: Electrical Properties Of Tissuesmentioning
confidence: 99%
“…A practical and time-efficient alternative is to increase the effective thermal conductivity of the fluid. This strategy was shown to approximate the thermal effect of fluid dynamics fairly well [250,272]. We included this strategy to account for convective heat transfer in the urinary bladder, which we modelled to have zero perfusion and thermal conductivity 10 times higher than the literature value [200,250,272].…”
Section: Electrical Properties Of Tissuesmentioning
confidence: 99%
See 1 more Smart Citation